Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12880-023-00991-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-radiomics models based on plain X-rays for prediction of lung metastasis in patients with osteosarcoma

Abstract: Objectives Osteosarcoma (OS) is the most common primary malignant bone tumor in adolescents. Lung metastasis (LM) occurs in more than half of patients at different stages of the disease course, which is one of the important factors affecting the long-term survival of OS. To develop and validate machine learning radiomics model based on radiographic and clinical features that could predict LM in OS within 3 years. Methods 486 patients (LM = 200, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Among all the distant metastases of osteosarcoma, lung metastases are the most common, and distant metastases have become an important factor affecting survival and prognosis [36]. Ping Yin et al [37] evaluated the predictive performance of a radiomics model of lung metastasis of osteosarcoma using multiple modeling methods based on X-ray images. Multivariate logistic regression analysis showed that alkaline phosphatase (ALP) was an important independent factor for predicting lung metastasis in osteosarcoma patients.…”
Section: Predicting Distant Metastasis Of Osteosarcomamentioning
confidence: 99%
“…Among all the distant metastases of osteosarcoma, lung metastases are the most common, and distant metastases have become an important factor affecting survival and prognosis [36]. Ping Yin et al [37] evaluated the predictive performance of a radiomics model of lung metastasis of osteosarcoma using multiple modeling methods based on X-ray images. Multivariate logistic regression analysis showed that alkaline phosphatase (ALP) was an important independent factor for predicting lung metastasis in osteosarcoma patients.…”
Section: Predicting Distant Metastasis Of Osteosarcomamentioning
confidence: 99%